Me looking at you, looking at me: The stare-in-the-crowd effect and autism spectrum disorder. (August 2021) - Crehan, Eileen T.; Althoff, Robert R.
Abstract: Introduction: The stare-in-the-crowd (SITC) effect describes the ability to detect self-directed gaze in a crowd. Given the importance of gaze detection in initiating and maintaining social interactions, there is a need to better characterize the SITC effect. Methods: Autistic and neurotypical young adults were presented with four SITC conditions. Eye tracking outcomes and arousal were compared by diagnosis and condition using repeated measures analysis of variance. Hierarchical regression was used to explore behavioral measures. Results: Significant interaction of diagnosis and condition was found for eye tracking outcomes. Overall, autistic participants exhibited less looking than neurotypical participants. Interest area dwell time, fixation count, and second fixation duration were significantly higher for conditions with shifting gaze, as well as conditions with more self-directed gaze across participants. Two hierarchical regression models of gaze behaviors with advanced theory of mind as a predictor were significant. Discussion: Autistic individuals respond to various gaze conditions in similar patterns to neurotypical individuals, but to a lesser extent. These findings offer important targets for social interventions. Highlights: Social perception plays a significant role in successful social interaction. Study of complex perceptual processes such as the stare in the crowd effect can provide insight into social challenges. Neurotypical and autistic adults demonstrated similar looking patterns in response to the stare in the crowd effect. Autistic adults demonstrated less overall gaze, revealing targets for interventions and screening. Autistic traits across the full participant pool were significant in models of gaze behavior.